What did the Romans ever do for us? ’Next generation’ networks and hybrid learning resources - Thomas, Elaine; Walker, Steve; Richardson, Paul (Proceedings of the International Conference on Networked Learning, 2012)
Networked learning is fundamentally concerned with the use of information and communication technologies (ICT) to link people to people and resources, to support the process of learning. This paper explores some current and forthcoming changes in ICT and some potential implications of these developments for networked learning. Whilst we aim to avoid taking a technologically determinist stance, we explore the potential for future practice and how some educational and pedagogic practices are evolving to exploit and shape the digital environment. We argue that we can change both the ways in which connections between people (learners and other learners; learners and tutors) are made and the nature of the resources that learning communities (particularly distributed communities) can engage with. In doing this we draw on two strands of work. Firstly, we draw on the ‘IBZL Education’ a UK Open University initiative to develop new scholarship in the context of STEM (Science, Technology, Engineering and Mathematics) through which educators are encouraged to think about technological change in the next five to ten years and ways in which we can intervene and shape these developments. We use problem-based learning as an example of a learning experience that can be difficult to implement in a networked learning environment. IBZL identified two broad strands of significant technological development. ’Superfast’ broadband networks that are capable of supporting novel applications are being rolled in the UK (and elsewhere). Also, boundaries between the real and virtual worlds are becoming blurred as in the ‘internet of things’ where, for example, RFID tags enable information about the real world to be brought into the virtual one. We use the term ‘artefact’ to describe designed components, whether entirely digital, such as a computer forum, or material, such as a tablet PC. Networked ‘hybrid’ technologies of virtual and material components have may great potential for use in education. Secondly, we illustrate how these changes may be beginning to happen in distance education using the example of TU100 My Digital Life, a new introductory Open University. . TU100 Students use an electronics board in their own homes to work on a programming problem in collaboration other students through a tutor-led tutorial in a web conferencing system. We also note some of the evident complexity that establishing such resources as part of wider infrastructures of networked learning would be likely to involve.